Faktor yang Berkaitan dengan Rendahnya Keikutsertaan Wanita Usia Subur dalam Pemeriksaan Inspeksi Visual Asam Asetat - Witri Alya; Fitri Yuliana; Kunti Nastiti (Pusat Riset dan Inovasi Nasional, 2023)
One of the easiest ways to detect cervical cancer early is with a visual examination of acetic acid. Early detection of cervical cancer by visual examination with acetic acid is guaranteed by the government, namely BPJS Kesehatan, and is included in the national health insurance program. The purpose of the study was to determine the low participation of women of childbearing age in acetic acid visual examination by UPT Puskesmas Timpah. The method used in this study is descriptive research. Questionnaires made by purposive sampling technique are used as data collection instruments; The maximum number of samples in the study sample is 30 samples. The respondents of this study were women of childbearing age. The results showed that based on respondents' knowledge of information, 26 respondents were uninformed (86.66%), 20 respondents (93.33%) did not support men. In the field of education, 21 people were found to have elementary and junior high school education as much as 70%, in the support of officers it was found that 20 people did not support (66.67%). Regarding access to information, it is known that 22 people did not get any assistance to get information (73.33%).